Hubungan antara Fatty Liver dengan Hipertensi Sistemik di RSUD Dr. Moewardi Surakarta - Belawati, Yeny Ristaning; ., Widiastuti; ., Balgis (Nexus Kedokteran Klinik, 2012)
Background: Fatty liver is the accumulation of fat in the liver ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. Patients fatty liver is often associated with metabolic disorders. It can be seen from the results of laboratory tests of blood, such as elevated levels of Alanin Amino Transferase (ALT), Gamma Glutamyl Transferase (GGT), alkaline phosphatase, ferritin, and another impaired liver function test. Hypertension is one of the conditions of metabolic disorders, and by an unknown mechanism there was an allegation of relationship between fatty liver and systemic hypertension Methods: This study was an analytical observational research with cross-sectional approach. The research was taken place in Radiology Installation of RSUD Dr. Moewardi Surakarta. The samples were consisted of 20 fatty liver patients and 20 non-fatty liver patients. Dependent variable of this research was fatty liver, and independent was systemic hypertension. The data was collected by viewing the result of USG abdomen-hepar examination and measuring patientâs blood pressure by researcher. The data of research was analyzed using Chi Square test and Odds Ratio. Results: There was a significant relationship between fatty liver and hypertension systemic in RSUD Dr. Moewardi Surakarta (p < 0,05); fatty liver patients had risk of hypertension systemic 7 times higher than the non-fatty liver patients (OR = 7) Conclusions: There was a significant relationship between fatty liver and hypertension systemic in RSUD Dr. Moewardi Surakarta, fatty liver patients have a risk of systemic hypertension 7 times greater than non-fatty liver patients Keywords: Fatty Liver, Hypertension Systemic, USG Abdomen Â